Good Corporate Governance, Leverage, Ukuran Perusahaan Dan Tax Avoidance - kushariadi, briska; putra, rosyid nur (IAIN Surakarta, 2018)
Tax avoidance is effort to minimize the tax burden are still in the realm of tax law.The purpose of this study was to determine the influence of good corporate governance, leverage, and firm size against tax avoidance. Indicator of corporate governance that are used to test are proportion of independent commissioners and audit quality. In this study, tax avoidance is measured using the effective tax rate (ETR). The number of samples analyzed 120 samples of companies listed on Indonesia Sharia Stock Index (ISSI) 2012-2016. Sample determination using purposive sampling technique. The data used in this research is a secondary data. Data were analyzed using panel regresion analysis with eviews 9. Result of analysis showed the pro- portion of independent commissioners and audit quality has no effect on tax avoidance. Leverage has positive influence on tax avoidance. While, firm size has negative influence on tax avoidance. Keywords: tax avoidance, proportion of independent commissioners, audit quality, leverage, firm size JEL Classification: G38, H26,L22,L25